The Importance of Leadership: Insights from Major Business Leaders in Maine - Silka, Linda (Maine Policy Review, 2018)
Susan Corbett, chief executive officer for Axiom Technologies, Kimberly A. Hamilton, president of Focus Maine, and Peter Triandafillou, vice president of Woodlands for Huber Resources Corporation share their ideas and insights on leadership as they respond to a series of questions about their own experiences in leadership and what they see as emerging challenges or opportunities that leaders face in Maine.
Keywords: business leadership; Maine; Susan Corbett; Axiom Technologies; Kimberly Hamilton; Focus Maine; Peter Triandafillou; Huber Resources